2009
DOI: 10.2307/20650281
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Service Level Agreements in Relational Management of Information Technology Outsourcing: An Empirical Study

Abstract: This study extends the view that formal contracts and relational governance function as complements rather than as substitutes. We investigate how specific characteristics of service level agreements (SLAs) impact relational governance in information technology outsourcing relationships. Eleven contractual elements (categorized into three SLA characteristics: foundation, change, and governance characteristics) are hypothesized to act as complements of three relational governance attributes: relational norms, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
342
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(386 citation statements)
references
References 84 publications
15
342
1
3
Order By: Relevance
“…We first assessed the second-order construct of trusting beliefs by comparing two separate models (Goo et al 2009). Model 1 hypothesizes that a unidimensional first-order factor accounts for the variance among all measurement items of the second-order construct (trust in seller) in this study.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%
“…We first assessed the second-order construct of trusting beliefs by comparing two separate models (Goo et al 2009). Model 1 hypothesizes that a unidimensional first-order factor accounts for the variance among all measurement items of the second-order construct (trust in seller) in this study.…”
Section: Measurement Model Assessmentmentioning
confidence: 99%
“…Further, numerous studies supported opposing views debating whether relational governance and contractual governance act as complements or substitutes (e.g. Poppo and Zenger 2002;Carson et al 2006;Goo et al 2009;Tiwana 2010). Inspired by this debate, a recent study by Huber et al (2013) has demonstrated how relational and contractual governance act as complementary elements as well as substitution at different points during an outsourcing engagement.…”
Section: Strategic Innovation In the Context Of It And Business Procementioning
confidence: 99%
“…Indeed, various studies suggested that contractual and relational governance act as either complementary or substitute to each other (Tiwana 2010) hinting at the effect, either positive or negative, of contractual elements on the quality of the client-supplier relationships (Goo et al 2009). We therefore first discuss how the use of three contract types (i.e.…”
Section: The Role Of Relational and Contractual Governance In Achievimentioning
confidence: 99%
“…However, the decision to undertake these relationships is often based on multiple factors or contingencies; firms will often weigh the pros and cons of each relationship, and each firm will have its own ultimate deciding factors that lead it to initiate the relationship (Oliver, 1990;Lee, Miranda, & Kim, 2004;Goo et al, 2009). Firms tend to progress cautiously into relationships, sending signals as they progress, and define their evolution in stages, as step-by-step progress with the evaluation of potential partners and initial negotiations, and preliminary adaptation efforts (Larson, 1992;Dwyer, Schurr, & Oh, 1987).…”
Section: Interorganizational Relationshipsmentioning
confidence: 99%
“…Furthermore, interorganizational exchanges continue to increase in frequency and value. While these exchanges evolve and mature, with this evolution comes opportunism, a negative yet inevitable consequence of interorganizational exchange (Goo, Kishore, & Rao, 2009). Firms in today's volatile market strive to increase the value of their IT investments; in doing so, the current trends, and even the next generation of strategies, have come to emphasize collaborative partnerships in the form of interorganizational relationships.…”
Section: Introductionmentioning
confidence: 99%